Prehrana jadralcev - Podlogar, Tim (Šport (Ljubljana), 2018)
Although sailing is one of the most important olympic sports and is one of the oldest sports disciplines, it is relatively poorly covered in scientific literature. This article offers sports nutrition guidelines for sailors in olympic and youth classes for time of the competitions.
Keywords: jadranje; prehrana; športna prehrana; vodni športi